Namibian pre-service science teachers’ perspectives on environmental issues - KASANDA, Choshi; ZEALAND, Donovan; TAYLOR, Neil (Economic and Environmental Studies, 2020)
As with many countries worldwide, Namibia is, despite its relatively small population and stable government, facing some significant environmental problems. This research sought to determine how a group of potentially influential tertiary-level students perceived the state of the environment in Namibia. To this end, a cohort of 20 preservice science teachers were interviewed to determine their perceptions of the environmental issues facing Namibia. The majority of the cohort identified deforestation as the major such issue. They also associated this concern with other problems such as soil erosion, salinity, and desertification. Some also raised concerns about global warming and associated climate change; several of the preservice teachers believed the country was already experiencing the effects of this. Although the population of Namibia is quite small relative to its area, the future teachers perceived population growth as a problem contributing to both environmental and social problems. All viewed education as key to reducing family size and alleviating social and environmental problems. However, none of the cohort made any connection between increasing patterns of consumption and environmental degradation.